(–)-β-Homoarginine anhydride, a new antioxidant and tyrosinase inhibitor, and further active components from Trichosanthes truncata. Issue 16 (17th August 2020) - Weng, I-Ting; Lin, Yen-An; Chen, Guan-Yu; Chiang, Hsiu-Mei; Liu, Yi-Jung; Chen, Chao-Jung; Lan, Yu-Hsuan; Lee, Chia-Lin
Abstract: One new amino acid derivative, (–)-β-homoarginine anhydride 1, as well as nine known compounds were isolated from Trichosanthes truncata . The structures of the isolates were elucidated by spectroscopic methods. Among them, compounds 5 and 11 could notably dose-dependently inhibit ROS productions in HaCaT keratinocyte cells without cytotoxicity in the concentration range of 0.2–20 μM. In cell-free mushroom tyrosinase assay, compounds 1 –5, 10 and 11 had more potential anti-tyrosinase activities with IC50 values of 106.9–255.6 μM than arbutin that were similar to predicted values of binding affinity calculated by molecule docking. The most active 2 had hydrogen bonds (Ser77, Glu309, Phe454) and electrostatic charges (Glu309, Glu248) interactions with mushroom tyrosinase, respectively. Our data manifested that T. truncata and its components are potentially to be developed as anti-aging and whitening agents for skin disorders. Graphical Abstract: